Effectiveness of Video Assisted Teaching on Knowledge and Practice Regarding Burping Technique of Newborn among Primi Postnatal Mothers - Bhandari, Diksha; Karn , Basant Kumar (Journal of Nobel Medical College, 2025)
Background: Burping is the release of gas from the upper digestive tract (esophagus and stomach) through the mouth. Burping baby is a key part of baby’s feeding routine. When baby swallows, air bubbles can become trapped in the stomach and cause discomfort. Burping allows baby to remove some of that gassiness to relieve the pain. It also helps prevent spitting up and provides the comfort. The objective of the study was to assess the effect of video assisted teaching on knowledge and practice regarding burping technique of newborn among primi-postnatal mothers.Materials and Methods: The study was conducted by adopting a pre-experimental design among 51 primi-postnatal mother of post-natal ward, neonatal ward and MCH Ward. Primi-postnatal mothers who fulfilled the inclusive criteria were selected by purposive sampling. A semi-structured interview questionnaire was used to assess the level of knowledge and practice. The tool was explained in detail and the pre-test was conducted. Video-assisted teaching on burping technique was conducted for the primi postnatal mothers and then the post-test was conducted after the 2 weeks of pre-test with the help of same semi structured interview questionnaire.Results: The findings of the study revealed that the overall mean improvement showed both knowledge and practice. A paired t-value of knowledge 11.01, which was statistically significant at (P < 0.001) level and similarly a paired t-test value of practice was 13.13, which was statistically significant at (P